A Sectoral Analysis of Foreign Direct Investment on the Economic Growth of Nepal - Phuyal, Ram Kumar; Sunuwar, Seema (Journal of Business and Social Sciences Research, 2019)
The role of foreign direct investment (FDI) on the economic growth is widely concerned in terms of increase in employment opportunities and for overall economic welfare, especially in developing nations like Nepal. On this context, this paper makes an attempt to examine the sector wise effects of FDI uneconomic growth in Nepal represented by gross domestic product (GDP) and FDI as dependent and independent variables respectively, thereby identifying the direct effect of FDI on GDP using 10 years (2007 to 2016) sect oral data as main source of the information. The entire result of the inferential analysis predicts that FDI of industry, tourism and agriculture sectors have a very positive and significant impact on GDP during the stipulated timeframe. In this line, findings suggest that the main stakeholders and government have to come up with new policy to open up foreign investment in other sectors as well which helps to move informal activities into formal economy. Finally, it is noted that formulation of new plan and policy will be a necessary condition but nonsufficient step for the development, so the key recommendations are made for the effective steps and actions to be taken by the concerned authority to review and implement the introduced plan and policies, which in turn, will help in flow of FDI to achieve, accelerate, and sustain the high rate of economic growth in Nepal.